Civil society engagement in innovation and research through the European Public Health Association - Paget, Dineke Zeegers (2013)
Background: The European Public Health Association (EUPHA) proposed and led PHIRE (Public Health Innovation and Research in Europe), with co-financing by the European Commission, to assess public health innovation and research at national level in Europe. PHIRE was also designed to promote organizational development and capacity building of EUPHA. We assess the success and limitations of using EUPHA’s participative structures. Methods: In total, 30 European countries were included—27 EU countries, Iceland, Norway and Switzerland. EUPHA thematic section presidents were asked to identify country informants to report, through a web-based questionnaire, on eight public health innovations. National public health associations (EUPHA member organizations) were requested to identify their national public health research programmes and calls, review the health research system, coordinate a stakeholder workshop and provide a national report. The section and national reports were assessed for responses and completeness. Results: Half of the final responding CIs were members of EUPHA sections and the other half gained from other sources. Experts declined to respond for reasons including lack of time, knowledge of the innovation or funding. National public health associations held PHIRE workshops with Ministries of Health in 14 countries; information for 10 countries was gained through discussions within the national association, or country visits by PHIRE partners. Six countries provided no response. Some national associations had too weak organizational structures for the work or insufficient financial resources or criticism of the project. Conclusion: EUPHA is the leading civil society organization giving support to public health research in Europe. PHIRE created new knowledge and supported organizational development. EUPHA sections gained expert reports on public health innovations in European countries and national public health associations reported on national public health research systems. Significant advances could be made if the European Commission worked more directly with EUPHA’s expert members and with the national public health associations.